Improving Energy Efficiency in Cluj-Napoca, Romania - Mot, Manuela; Bose, Ranjan; Burduja, Sebastian; Ionescu-Heroiu, Marcel (World Bank, Washington, DC, 2016)
The main impetus for this report (and for the reports prepared for the other six growth poles) is a request received from the Ministry of Regional Development and Public Administration. The request came within the context of on-going preparations for the 2014-2020 programming period, with energy efficiency being one the major themes of the Europe 2020 strategy, and a critical priority for all EU member countries. Within Romania, local authorities that will want to access energy efficiency funds under the 2014-2020 Regional Operational Program will need to first prepare energy efficiency strategies. The TRACE tool is specifically targeted at local authorities, and is a good instrument for drafting such strategies after the 1989 Revolution; Romania began its transition from a centralized system to a market-run economy. Today the country is a member of the European Union (EU) and NATO. After more than a decade of economic restructuring and political change, the country has taken significant steps to catch up with the economic performance of more developed EU countries. Although radical reforms brought about significant changes, the standard of living of Romanians is still behind the EU average. Cluj-Napoca (Cluj) is one of cities where such disparities are less pronounced, as the region is more developed and prosperous than most regions in the country. Cluj has developed quite well in the past few years, and it has become one of the most flourishing cities in the country, having a good growing potential. At present, the city is an important economic center, home to several local brands that have become famous nationwide as well as in Europe. Moreover, Cluj is known today as the 'capital' of the IT sector in the country, due to an aggressive expansion of this field in recent years.